2020
DOI: 10.1097/gme.0000000000001599
|View full text |Cite|
|
Sign up to set email alerts
|

A selective serotonin receptor agonist for weight loss and management of menopausal vasomotor symptoms in overweight midlife women: a pilot study

Abstract: study concept and design, analysis and interpretation of data, drafting and revising the paper, and have seen and approved the final version of the manuscript. EK-Dr. Kapoor was the co-principal investigator on the study. She contributed to development of the study protocol, recruitment of participants, and their follow-up in the study. She is the primary author of the manuscript._SSF -Dr. Faubion was a co-principal investigator for the study. She and Dr. Croghan collaborated in obtaining funding for the study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 50 publications
(51 reference statements)
0
2
0
Order By: Relevance
“…33 In an open-label single-arm pilot study of a weight-loss medication (selective serotonin 2C [5-HT2C] receptor agonist) tested in 20 women, after 12-weeks there were both a decrease in weight and significant improvement in VMS (decline, 5.4 hot flashes/d) from baseline to week 12. 37 The study also found that after the weight-loss medication was stopped, there was a rapid increase in VMS with a return to baseline weight, further supporting the notion that weight loss improved VMS. However, these studies are either small pilot studies, nonrandomized trials, or post hoc analyses of studies designed for a different purpose.…”
Section: Weight Lossmentioning
confidence: 60%
See 1 more Smart Citation
“…33 In an open-label single-arm pilot study of a weight-loss medication (selective serotonin 2C [5-HT2C] receptor agonist) tested in 20 women, after 12-weeks there were both a decrease in weight and significant improvement in VMS (decline, 5.4 hot flashes/d) from baseline to week 12. 37 The study also found that after the weight-loss medication was stopped, there was a rapid increase in VMS with a return to baseline weight, further supporting the notion that weight loss improved VMS. However, these studies are either small pilot studies, nonrandomized trials, or post hoc analyses of studies designed for a different purpose.…”
Section: Weight Lossmentioning
confidence: 60%
“…Weight loss may have greater effects in reducing VMS when women are earlier in the transition 33 . In an open-label single-arm pilot study of a weight-loss medication (selective serotonin 2C [5-HT2C] receptor agonist) tested in 20 women, after 12-weeks there were both a decrease in weight and significant improvement in VMS (decline, 5.4 hot flashes/d) from baseline to week 12 37 . The study also found that after the weight-loss medication was stopped, there was a rapid increase in VMS with a return to baseline weight, further supporting the notion that weight loss improved VMS.…”
Section: Lifestylementioning
confidence: 99%